The Influence of Job Involvement and Organizational Commitment on Job Satisfaction of Civil Servants at the UPTD Public Health Center of Sungai Ambawang - Nur Aisiyah Siregar; Devi Yasmin (SAINTIS Publishing, 2025)
This study aims to analyze the influence of Job Involvement and Organizational Commitment on Job Satisfaction of Civil Servants at the UPTD Public Health Center of Sungai Ambawang. The method used is an associative approach with primary data collected through interviews and questionnaires distributed to 49 civil servants at the UPTD Public Health Center of Sungai Ambawang. Secondary data was used to support the analysis. The results of the study indicate that Job Involvement and Organizational Commitment have a positive and significant effect on Job Satisfaction. Based on the multiple linear regression results, it was found that Job Involvement (b1 = 0.360) and Organizational Commitment (b2 = 0.262) positively affect Job Satisfaction, with a coefficient of determination (R²) of 0.596, which indicates that 59.6% of the variation in Job Satisfaction can be explained by the two independent variables. The simultaneous test (F-test) shows that both variables significantly influence Job Satisfaction. In addition, the partial test (t-test) shows that both variables individually have a significant effect on Job Satisfaction. This study suggests that the leadership at the UPTD Public Health Center of Sungai Ambawang should strengthen organizational commitment and job involvement to improve job satisfaction and the quality of services provided to the community. For future research, it is recommended to consider additional variables, such as work-life balance or organizational culture, and explore longitudinal studies to better understand the long-term impact of Job Involvement and Organizational Commitment on Job Satisfaction and employee retention.